Pelatihan pembuatan media baca dan penerapan strategi lead reading bagi siswa kelas awal di Kabupaten Bantaeng - Widya Karmila Sari Achmad; Muhammad Irfan (DEDIKASI, 2020)
The purpose of the desired activity is to introduce ways of using and making reading media and the application of lead reading strategies for elementary school teachers in Kabupaten Bantaeng because most primary school teachers have difficulty in making media read and implementing appropriate strategies for students regarding reading. This is due to the lack of media availability and how to use it is not equipped. The method used in the service is the delivery of material in lectures and demonstrations, the practice of making teaching aids by the participants, and the practice of using the teaching aids by groups of participants. The product produced during service is read media.